Effect of phosphorus on interface characterization of steel–copper bimetals in solid–liquid composite casting. (March 2022) - Kang, Yuanyuan; Zhang, Guowei; Xu, Hong; Niu, Jingwei
Abstract: Carbon steel and Cu-Pb-Sn bimetallic samples were prepared by the solid–liquid composite method. The preheating temperature of the steel matrix was 1150 ± 30 °C and the Cu-Pb-Sn alloy smelting temperature was 1200 ± 20 °C. The Cu-Pb-Sn alloy was subsequently poured into the preheated steel matrix to form a bimetallic composite interface. The influence of phosphorus (P) on the microstructure and mechanical properties of the interface and the behavior mechanism of P at the bimetallic interface were examined. The results showed that when the P content was 0.1% (all contents reported herein are in wt%), the carbon steel and Cu-Pb-Sn alloy formed an ideal metallurgical bonding interface. It was found that a nanoscale Fe3 P phase was precipitated at 750 °C at the grain boundary of the ɑ-Cu interface. The Fe3 P interplanar spacing of the phase was 2.1 Å, and the interplanar spacing of ɑ-Cu was 2.07 Å. When the P content reached 0.2%, the Fe3 P phase precipitated at 1020 °C and aggregated into micrometer size at the interface, which formed a transition zone with ɑ-Cu. The transition zone widened with an increase in the P content in the alloy liquid. The interface atomic diffusion distance between Fe and Cu was 11.55 µm when the P content was 0.1%, and the sample shear strength reached a maximum value of 157.89 MPa. With increasing P content, the interface became hard and brittle because it emerged in the precipitated transition zone, which decreased the shear strength. Graphical Abstract: ga1 Highlights: Bimetallic materials fabricated by solid-liquid composites casting. Good metallurgical bonding was formed between steel and copper at the interface. The interdiffusion mechanism of Cu and Fe atoms at the interface was revealed through the FIB and TEM. The Fe / Cu interface was characterized by electron microscopy and EDS.